Reproductive innovation and the recognition of a new genus within the Polystomatidae (Monogenea) infecting chelonian vertebrates - Tinsley, Richard C (Folia parasitologica, 2017)
Polystomatid monogeneans have a wide diversity of life cycles correlated with the varied ecology and behaviour of their aquatic vertebrate hosts. Typically, transmission involves a swimming infective larva but most hosts are amphibious and invasion is interrupted when hosts leave water. A key life cycle adaptation involves a uterus that, in the most specialised cases, may contain several hundred fully-developed larvae prepared for instant host-to-host transmission. By contrast, one subfamily of the Polystomatidae - the Polystomoidinae, specific to chelonians (freshwater turtles) - has a simplified reproductive system without a uterus. Recently, Polystomoides nelsoni Du Preez et Van Rooyen, 2015 has been described with a uterus containing multiple eggs. The present study explores the exceptional interest of this parasite - for the functional biology of egg production, for the evolution of a reproductive system unique amongst ca 60 species in the subfamily, and for systematic relationships. A new genus is proposed, Uteropolystomoides gen. n., separate from the four currently-recognised genera Polystomoides Ward, 1917, Uropolystomoides Tinsley et Tinsley, 2016, Neopolystoma Price, 1939 and Polystomoidella Price, 1939 which lack a uterus. In addition, U. nelsoni (Du Preez et Van Rooyen, 2015) comb. n. has a suite of distinctive copulatory stuctures: a massive genital bulb with an exceptionally large number of very long genital spines and hyper-development of the vaginal openings. These characters set U. nelsoni apart from all other polystomoidines worldwide except Polystomoides multifalx Stunkard, 1924 and P. stunkardi Harwood, 1931. Missing data for these latter species preclude definitive assessment of inter-relationships but the distinguishing characters of U. nelsoni, especially the unique occurrence of the uterus, suggest a novel evolutionary pathway isolated from other lineages of polystomatids infecting chelonians.
Keywords: Animals; ovarium; rozmnožování; Trematoda; želvy; Female; biologická evoluce; infekce červy třídy Trematoda; Trematode Infections; ženské pohlaví; Reproduction; uterus; Uterus; Fresh Water; sladká voda; Parasite Egg Count; počet parazitárních vajíček; Turtles; zvířata; Biological Evolution; Ovary